The development of nature-inspired gripping system of a flat CFRP strip for stress-ribbon structural layout. Issue 2 (7th April 2021) - Gribniak, Viktor; Arnautov, Aleksandr K; Rimkus, Arvydas
Abstract: The elegant stress-ribbon systems are efficient in pedestrian bridges and long-span roofs. Numerous studies defined corrosion of the steel ribbons as the main drawback of these structures. Unidirectional carbon fiber-reinforced polymer (CFRP) is a promising alternative to steel because of lightweight, high strength, and excellent corrosion and fatigue resistance. However, the application of CFRP materials faced severe problems due to the construction of the anchorage joints, which must resist tremendous axial forces acting in the stress-ribbons. Conventional techniques, suitable for the typical design of the strips made from anisotropic material such as steel, are not useful for СFRP strips. The anisotropy of СFRP makes it vulnerable to loading in a direction perpendicular to the fibers, shear failure of the matrix, and local stress concentrations. This manuscript proposes a new design methodology of the gripping system suitable for the anchorage of flat strips made from fiber-reinforced polymers. The natural shape of a logarithmic spiral Nautilus shell describes the geometry of the contact surface. The continuous smoothly increasing bond stresses due to friction between the anchorage block and the CFRP strip surface enable the gripping system to avoid stress concentrations. The 3D-printed polymeric prototype mechanical tests proved the proposed frictional anchorage system efficiency and validated the developed analytical model. Graphical Abstract: